1997
DOI: 10.1021/om961069b
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Properties, and X-ray Crystal Structures of Iron and Ruthenium Compounds with the η5-C5Me4CF3Ligand. Compounds of the Type [(η5-C5Me4CF3)M(μ-CO)(CO)]2(M = Fe, Ru)

Abstract: (Trifluoromethyl)tetramethylcyclopentadiene, ΗC5Me4CF3 (Cp⧧H), reacts with Ru3(CO)12 in refluxing n-decane to produce [(η5-C5Me4CF3)Ru(μ-CO)(CO)]2 (1). In chlorinated hydrocarbon solutions, 1 reacts with the solvents in the presence of visible light to produce [(η5-C5Me4CF3)Ru(CO)2(Cl)] (3a). Compound 1 reacts with iodine in refluxing CH2Cl2 to produce [(η5-C5Me4CF3)Ru(CO)2(I)] (3b). The X-ray crystal structure of compound 3b is presented. Compound 3b reacts with triphenylphosphine in refluxing ethanol to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Because the switch of the Cp ligand in catalyst 1 to the bulkier and more electron-rich Cp* ligand in catalyst 2 + 2a engendered an increase in monoselectivity, we wondered whether steric or electronic factors lead to the change. We therefore made 4 (and ultimately 6 ) with the more electron-poor tetramethyl-(trifluoromethyl)­cyclopentadienyl (Cp ⧧ ) ligand, which has been shown to mimic the sterics of Cp* and the electronics of Cp. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the switch of the Cp ligand in catalyst 1 to the bulkier and more electron-rich Cp* ligand in catalyst 2 + 2a engendered an increase in monoselectivity, we wondered whether steric or electronic factors lead to the change. We therefore made 4 (and ultimately 6 ) with the more electron-poor tetramethyl-(trifluoromethyl)­cyclopentadienyl (Cp ⧧ ) ligand, which has been shown to mimic the sterics of Cp* and the electronics of Cp. , …”
Section: Resultsmentioning
confidence: 99%
“…The pentamethylcyclopentadienyl (Cp*) ligand is both more electron-rich and sterically bulky than the cyclopentadienyl (Cp) ligand. , Given the distinct differences in reactivity between Cp-containing catalyst 1 (which is fast but not positionally selective) and Cp*-containing 2 + 2a and 5 (which are selective for monoisomerization), we wanted to investigate whether the change in selectivity during catalysis is the result of steric or electronic influences between the Ru center and the alkene. Catalytic and structural comparisons between Cp- and Cp*Ru complexes have been undertaken, employing the 1-(trifluoromethyl)-2,3,4,5-tetramethylcyclopentadienyl (Cp ⧧ ) ligand developed by Gassman, reported to mimic the electronics of the Cp ligand and sterics of the Cp* ligand. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The dimers Cp* 2 Ru 2 (CO) 4 ( 1 ), Cp 2 Ru 2 (CO) 4 ( 2 ), (HB(pz) 3 ) 2 Ru 2 (CO) 4 ( 3 ), Ind 2 Ru 2 (CO) 4 ( 4 ), (Cp 2 CH 2 )Ru 2 (CO) 4 ( 6 ), and (Fv)Ru 2 (CO) 4 ( 8 ) 13 were prepared by literature methods. Cp ⧧ 2 Ru 2 (CO) 4 ( 5 ) was generously provided by J. H. Nelson at the University of NevadaReno …”
Section: Methodsmentioning
confidence: 99%
“…XPS studies of cyclopentadienide derivatives indicated that the addition of each methyl group to the Cp′ ligand lowers the binding energy of the inner shell electrons of a complexed metal by ∼0.08 eV, whereas one trifluoromethyl group raises the binding energy by ∼0.35 eV 49b. 52, 54 Preparation of [( η 5 ‐C 5 Me 4 CF 3 )RuCl(cod)] thus gave a complex with electronic properties nearly identical to [CpRuCl(cod)], while retaining the steric bulk otherwise provided by the Cp* ligand. The reactivity of this complex (Table 1, entry 11) was both underwhelming and strikingly similar to that of [Cp*RuCl(cod)] (compare entries 10 vs. 11).…”
Section: Resultsmentioning
confidence: 99%